Posted on

Solve for x example

Q:  Solve:  2(x + 3) + 3 = -3(3x + 1) – 3x

A:  OK, we start by distributing on both the left and the right to get rid of parentheses like so:

2(x + 3) + 3 = -3(3x + 1) – 3x

2x + 6 + 3 = -9x – 3 – 3x  [I mulitplied the 2 through on the left side…. and I multiplied the -3 through on the right side.. Make sense?]

Now, combine like terms:

2x + 9 = -12x – 3

Now, add 12x to both sides:

2x + 9 + 12x = -12x – 3 + 12x

Notice the -12x and the 12x on the right side will cancel out!

14x + 9 = -3

Subtract 9 from both sides:

14x + 9 – 9 = -3 – 9

14x = -12

Divide both sides by 14:

14x/14 = -12/14

x = -12/14 = -6/7

Leave a Reply